2008
DOI: 10.2109/jcersj2.116.1208
|View full text |Cite
|
Sign up to set email alerts
|

Estimation and confirmation of adsorption behavior of acrylic polymer on alumina from a molecular chemistry standpoint of adipic acid adsorption

Abstract: Adsorption of a low molecular carboxylic acid (adipic acid) on alumina was studied at molecular chemistry standpoint to estimate adsorption behavior of an acrylic polymer containing carboxylic acid group in water-base system. By the zeta potential measurement, adipic acid adsorbs on alumina chemically. The maximum amount of adsorption of adipic acid was observed at pH 5, which is close to pKa1 (4.41) and pKa2 (5.28) of adipic acid. In the region over pH 5, the adsorbed amount decreased monotonously with increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…However, the present results indicate that some specimens show negative zeta potential even in the SBFs at pH 7.4 and the zeta potential did not simply decreased with increasing pH. It is reported that alumina can adsorb phosphate and carboxylate ions onto its surface to decrease the surface zeta potential [33,34]. In fact, an EDX peak of phosphorus was detected in the samples after soaking in 1.5SBF for 7 days (see Table 1).…”
Section: Discussionmentioning
confidence: 49%
“…However, the present results indicate that some specimens show negative zeta potential even in the SBFs at pH 7.4 and the zeta potential did not simply decreased with increasing pH. It is reported that alumina can adsorb phosphate and carboxylate ions onto its surface to decrease the surface zeta potential [33,34]. In fact, an EDX peak of phosphorus was detected in the samples after soaking in 1.5SBF for 7 days (see Table 1).…”
Section: Discussionmentioning
confidence: 49%